The Satellite DNAs Populating the Genome of Trigona hyalinata and the Sharing of a Highly Abundant satDNA in Trigona Genus - Pereira, Jaqueline A.; Cabral-de-Mello, Diogo C. [UNESP]; Lopes, Denilce M. (MDPI, 2023)
Among Meliponini species, c-heterochromatin can occupy large portions of chromosomes. This characteristic could be useful for understanding evolutionary patterns of satellite DNAs (satDNAs), although few sequences have been characterized in these bees. In Trigona, phylogenetically represented by clades A and B, the c-heterochromatin is mostly located in one chromosome arm. Here we used different techniques, including restriction endonucleases and genome sequencing followed by chromosomal analysis, to identify satDNAs that may be contributing to the evolution of c-heterochromatin in Trigona. Our results revealed a highly abundant ThyaSat01-301 satDNA, corresponding to about 13.77% of the Trigona hyalinata genome. Another seven satDNAs were identified, one corresponding to 2.24%, and the other six corresponding to 0.545% of the genome. The satDNA ThyaSat01-301 was shown to be one of the main constituents of the c-heterochromatin of this species, as well as of other species belonging to clade B of Trigona. However, this satDNA was not observed on the chromosomes of species from clade A, demonstrating that the c-heterochromatin is evolving divergently between species of clade A and B, as a consequence of the evolution of repetitive DNA sequences. Finally, our data suggest the molecular diversification of the karyotypes, despite a conservated macrochromosomal structure on the genus.
Keywords: bees; c-heterochromatin; genome; Meliponini; RepeatExplorer